Penatalaksanaan Holistik Ibu Hamil Usia Remaja dengan Anemia Melalui Pendekatan Dokter Keluarga - Ramadirga Thio Saba; TA Larasati (Majority, 2020)
Adolescent pregnancy is a global problem that occurs throughout the world. Pregnancy in adolescents poses a high risk to the health of both mother and baby. One of the risks of adolescent pregnancy is anemia. The state of anemia in adolescent pregnancy requires holistic management including patient's physical and psychological condition.This study is a case report. Primary data is obtained through anamnesis, physical examination, and home visits. Secondary data is obtained from the patient's medical records. Assessment based on holistic diagnosis from the beginning, process, and end of the study in a quality and quantitative way. Female patients in their teens conceived the first child at 27 weeks pregnant with body complaints felt limp, nausea, lack of appetite and dizziness felt early in pregnancy. Food intake during pregnancy is reduced due to frequent nausea and vomiting and can only eat with small portions and a rare frequency. Weight loss is ideal based on the calculation of the patient's BMI and the nutritional status of the patient based on LILA including normal. In patients there is an anemis conjunctiva. The patient's hemoglobin (Hb) levels are 9 g/dL which is relatively low for the II trimester. Enforcement of diagnosis and management in these patients has been done holistically, patient centered, family approach and in accordance with national guidelines and based on evidence based medicine. Changes in patient and family knowledge and behavior occur after patient centre and family approach interventions.